PENERAPAN STRATEGI GENIUS LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 14 PEKANBARU - Vivin Desvionita; Maria Erna; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to know the improve of students learning achievement by using Genius Learning strategy on the topic of the Structure of Atoms and the Periodic Systems of Elements in class X senior high school (SMAN) 14 Pekanbaru. This research was experimental research with pretest-postest design. The sample of this research were students of class X4 as the experimental research and students of class X3 as a control class that has been randomly selected after a test of normally and homogenity test. Experiment class is a class that is applied Genius Learning strategy while the control class was not. Data analysis technique used is t-test. Based on analysis of the data obtained tcount> ttable is 2,15>1,67, it is mean that the apllication of Genius Learning strategy can improved students learning achievement on the topic of the Structure of Atoms and the Periodic Systems of Elements in class X senior high school (SMAN) 14 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,72. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,54. Genius Learning strategy can activate the students in learning process to improve the students achievement in learning.Keywords : Learning Achievement, Genius learning, Structure of Atoms and Periodic Systems